A Rejoinder to Godden (1995) and Searston (1995) - Jonathan P. Sher (Journal of Research in Rural Education, 1995)
When Ted Coladarci, JRRE editor, called me to say he had just received a very lengthy response to "Beyond the Conventional Wisdom: Rural Development as if Australia's Rural People and Communities Really Mattered" (Sher & Sher, 1994), I was pleased. When he told me it had been written by an agricultural economist at the University of Sydney, my sense of pleasurable anticipation increased. After all, my wife (Katrina) and I wrote this paper to encourage discussion of the issues involved-and now an academic from a respected institution had made the effort to write much more than a brief reply.